Strategi Penetapan Harga Penawaran untuk Memenangkan Tender pada PT.Vidya Radeva Artha - Ayu Ika Puri; Sayu Kadek Jelantik (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
The purpose of the study was to determine the form of pricing strategy, the implementation of pricing strategy and the implications of the bidding pricing strategy to win the tender at PT. Vidya Radeva Artha. The research methodology used a descriptive qualitative method, with observation, interview, and documentation data collection techniques. The results of this study consist of three important points, namely: The form of the bidding pricing strategy to win the tender at PT. Vidya Radeva Artha, namely the cost-plus pricing strategy, the value-based pricing strategy, and the penetration pricing strategy (low pricing). The process of the bidding pricing strategy to win the tender at PT. Vidya Radeva Artha is from the cost of goods added to other costs which are then carried out by increasing the profit margin by 10% -60%. The implications of the cost-based pricing strategy are carried out for middle-type tenders, namely tenders with quantities that are neither large nor small, the cost-based pricing strategy is carried out for special custom tenders from PT. Trakindo, namely tenders with quantities that are not large but are certain to win the tender, and finally the penetration pricing strategy is carried out for consumer goods tenders with quantities that are large compared to other tenders.